ANALISIS DALAM MEMANAJEMEN KEBUTUHAN SISWA LEWAT ASESMEN NON TES DCM DALAM PENYUSUNAN PROGRAM TAHUNAN DAN SEMESTERAN DI SMPN 29 SURABAYA - Widya Anggraeini.S.; Nikita Variska.P.S.; Ayu Jingga Arisa; Elisabeth Christiana (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
The Problem Checklist (DCM) is a questionnaire that contains a number of questions in the form of statements related to problems that are assumed to frequently occur with students. The results of the questionnaire processing will help guidance and counseling teachers in designing counseling guidance programs to help students overcome the problems they experience in order to realize effectiveness, efficiency and achieve service targets. The aim of this research is to assist guidance and counseling teachers in implementing guidance and counseling programs, namely annual guidance and counseling programs, and semester guidance and counseling programs that are appropriate and in accordance with student needs. This provides a structured overview of management in providing guidance and counseling services for students. This type of research is descriptive research.  The sample determination method uses DCM non test analysis.